Highly Controlled Ring-Opening of Siloxydifluorocyclopropanes: A Versatile Route to Cyclic Fluoroketones - Kageshima, Yoshiya; Suzuki, Chiharu; Oshiro, Kojun; Amii, Hideki (Synlett, 2015)
A convenient access to cyclic fluoroketones that involves base-promoted ring-opening of siloxydifluorocyclopropanes is presented. Selective formation of gem-difluorinated cycloalkanones and monofluorinated enones has been achieved.
Keywords: fluorine; silicon; cyclopropane; ring-opening; ketone